Poemas - Natalia Urzúa (L'Ordinaire des Amériques)
Natalia Urzúa (Santiago de Chile, 1985) is a Chilean musician, songwriter, and decimist living in France. As a member of various poetic-musical groups, she shares her knowledge of popular and traditional Latin American culture between the two continents. She is a member of the collective that published, in 2019, La décima feminista, a poetic anthology.